Impact of Incomplete Percutaneous Revascularization in Patients With Multivessel Coronary Artery Disease: A Systematic Review and Meta‐Analysis. Issue 12 (16th December 2016) - Nagaraja, Vinayak; Ooi, Sze‐Yuan; Nolan, James; Large, Adrian; De Belder, Mark; Ludman, Peter; Bagur, Rodrigo; Curzen, Nick; Matsukage, Takashi; Yoshimachi, Fuminobu; Kwok, Chun Shing; Berry, Colin; et al.
Abstract : Background: Up to half of patients undergoing percutaneous coronary intervention have multivessel coronary artery disease (MVD) with conflicting data regarding optimal revascularization strategy in such patients. This paper assesses the evidence for complete revascularization (CR) versus incomplete revascularization in patients undergoing percutaneous coronary intervention, and its prognostic impact using meta‐analysis. Methods and Results: A search of PubMed, EMBASE, MEDLINE, Current Contents Connect, Google Scholar, Cochrane library, Science Direct, and Web of Science was conducted to identify the association of CR in patients with multivessel coronary artery disease undergoing percutaneous coronary intervention with major adverse cardiac events and mortality. Random‐effects meta‐analysis was used to estimate the odds of adverse outcomes. Meta‐regression analysis was conducted to assess the relationship with continuous variables and outcomes. Thirty‐eight publications that included 156 240 patients were identified. Odds of death (OR 0.69, 95% CI 0.61‐0.78), repeat revascularization (OR 0.60, 95% CI 0.45‐0.80), myocardial infarction (OR 0.64, 95% CI 0.50‐0.81), and major adverse cardiac events (OR 0.63, 95% CI 0.50‐0.79) were significantly lower in the patients who underwent CR. These outcomes were unchanged on subgroup analysis regardless of the definition of CR. Similar findings were recorded when CR was studied in the chronic total occlusion (CTO) subgroup (OR 0.65, 95% CI 0.53‐0.80). A meta‐regression analysis revealed a negative relationship between the OR for mortality and the percentage of CR. Conclusion: CR is associated with reduced risk of mortality and major adverse cardiac events, irrespective of whether an anatomical or a score‐based definition of incomplete revascularization is used, and this magnitude of risk relates to degree of CR. These results have important implications for the interventional management of patients with multivessel coronary artery disease.